Byron, Blake, and Heaven - Goldberg, Brian (Romanticism on the Net, 2002)
AbstractRomantic discussions of labor and leisure are often tied to descriptions of the afterlife. In the depictions of heavenly leisure and labor with which this essay is concerned—Blake's "The Little Black Boy" and "The Chimney Sweeper" of Innocence, Byron's Don Juan Canto II and Cain, and The Ghost of Abel, which is Blake's response to Cain—Blake derives his visions of the afterlife partially from the work of Emanuel Swedenborg, while Byron draws on Lucretius' version of Epicureanism. Despite their irreconcilable sources, however, the poets converge on a single idea. If heaven is to relieve us of the distinction between labor and leisure, thus lifting Adam's curse while overcoming a merely conventional division of human activity, it will also have to erase the boundary between physical and mental work. In these poems, Byron and Blake each stage acts of phronesis, of moral judgment unregulated by statute or decree, in order to bring their theories of heaven in contact with the facts of life.